2020
DOI: 10.1103/physrevd.102.035015
|View full text |Cite
|
Sign up to set email alerts
|

LSND constraints on the Higgs portal

Abstract: High-luminosity fixed target experiments provide impressive sensitivity to new light weakly coupled degrees of freedom. We revisit the minimal case of a scalar singlet S coupled to the Standard Model through the Higgs portal that decays visibly to leptons for scalar masses below the dipion threshold. The dataset from the LSND experiment is found to impose the leading constraints within two mass windows between m S ∼ 100 and 350 MeV. In the process, we analyze a number of scalar production channels in the targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…[11], which studied scalars produced only in B-decays, we find that the additional scalar production from kaon decays and proton bremsstrahlung can significantly expand the parameter space - that can be probed by DarkQuest. 7 In the figure, we also show the current experimental bounds on dark scalar parameter space, including those from CHARM [72,88], LSND [89], E787/E949 [90,91], LHCb [92,93], and NA62 [94]. In addition, we also display sensitivity projections from several ongoing or proposed future experiments, including NA62 [3,95], SBND and ICARUS [96], Belle II [97] (see also ref.…”
Section: Darkquest Sensitivity To Dark Scalarsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11], which studied scalars produced only in B-decays, we find that the additional scalar production from kaon decays and proton bremsstrahlung can significantly expand the parameter space - that can be probed by DarkQuest. 7 In the figure, we also show the current experimental bounds on dark scalar parameter space, including those from CHARM [72,88], LSND [89], E787/E949 [90,91], LHCb [92,93], and NA62 [94]. In addition, we also display sensitivity projections from several ongoing or proposed future experiments, including NA62 [3,95], SBND and ICARUS [96], Belle II [97] (see also ref.…”
Section: Darkquest Sensitivity To Dark Scalarsmentioning
confidence: 99%
“…[77] (see also ref. [89]) which employs the generalized Weizsacker-Williams method [78] to factorize the reaction to the two subprocesses: (i) emission of the scalar from the proton and (ii) proton-proton scattering. We denote the incoming proton momentum as p p , the fraction of the proton beam momentum carried by the emitted scalar as z = p S /p p with p S the scalar momentum, and the scalar transverse momentum as p T .…”
Section: A Direct Scalar Productionmentioning
confidence: 99%
“…Ref. [98] found that this production process is dominant for such a search at LSND (proton beam energy of 800 MeV). In contrast to the Z bremsstrahlung process, the scalar coupling is suppressed by the effective proton Yukawa coupling.…”
Section: Jhep07(2021)166mentioning
confidence: 99%
“…This parameter space is relevant for the explanation of the anomalous KOTO events. LSND [79] can also put constraints on this parameter space [80]. 3 [82,84,85], SHiP [82,86], Fermilab μbeam fixed target [82,87], and NA64μ; e [74,87].…”
Section: Light Scalarmentioning
confidence: 99%
“…Thus, the new physics explanation for the KOTO anomaly is required to generate three anomalous events and satisfy the GN bound. Several such solutions have been proposed in the literature [80,[130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Koto Anomalymentioning
confidence: 99%